Zes liederen - Baeyens, H. (Brussel : H. Baeyens, 1870)
Deze publicatie bevat volgende liederen
Zwaantje
Lenteliedje
Bij het Lijkje van een kind
De muggendans
Vleugelen
Het meest
Bibliotheek Camille Huysmans
Nederlands
Partituur
Keywords: liederen; partituren